Interval analysis for certified numerical solution of problems in robotics - Merlet, Jean-Pierre (Zielona Góra: Uniwersytet Zielonogórski)
Interval analysis is a relatively new mathematical tool that allows one to deal with problems that may have to be solved numerically with a computer. Examples of such problems are system solving and global optimization, but numerous other problems may be addressed as well.
Keywords: interval analysis; uncertainties; robotics